(Un)doing Marxism from the Outside. Issue 2 (2nd April 2016) - Chakrabarti, Anjan; Dhar, Anup; Cullenberg, Stephen
Abstract : The essay's focus is on the outside. The urgency of rethinking an outside to (global) capitalism stems from the need for critical reflection on two sets of ideas incumbent upon the South: one set marked by globality and the other marked by a continuum of terms such as "local, " "third world, " and "pre-capital." Such a critical reflection takes the essay to a rethinking of the given script of Marxism from the outside, reengaging with advanced Marxian reflections on questions of "hegemony" and psychoanalytic exegeses on questions of "foreclosure" (verwerfung). Interrogation of extant theorizations on hegemony and foreclosure lead both to more abstract considerations on the Lacanian symbolic and the real and also to apparently more concrete reflections on "global capitalism" and its outside: the "world of the third." Other than defamiliarizing the given script of capitalist development, this has the potential to open up new avenues to think of politics and subject.